(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
Speed and power abilities are the leading ones for achieving high results in modern boxing. At the same time, the selection of effective strategies for the development of high-speed and power abilities in boxers at the stage of specialised training has not been sufficiently studied. In this regard, the purpose of the research is to study the effectiveness of the programme of improvement of high-speed and power abilities of boxers at the stage of specialised training. Methods of the research: theoretical analysis and generalisation of data in scientific and methodical literature, pedagogical observation, methods of studying the level of development of physical qualities (chronodynamometry, method of control exercises), pedagogical experiment, methods of mathematical statistics. Results. With the help of the analysis of data of scientific and methodical literature the training program was developed, the main means of development of high-speed and power abilities were - the method of repeated exercises with the use of unsaturated burdens and with the limited number of repetitions (to failure), the method of repeated trainings with maximum and close to maximum efforts for creation of maximum muscular force and development of explosive force, the method of isometric efforts for development of force in a static state, performance of the most strong but slow blows in series of spurts (5 sp). Over time - the maximum possible performance of the tempo of blows and preservation of their strength, circuit training, which has a complex effect on a number of muscle groups. The exercises are performed at stations and are selected in such a way that each series works on different muscle groups. The second approach to improving the high-speed power abilities of boxers was to develop intra- and inter-muscular coordination. The individual characteristics of boxers, the impact of exercises on them, and the adjustment of the load to take into account individual characteristics and reactions to the proposed exercises were taken into account. The main condition was the performance of movements in compliance with their coordination structure and at a speed equal to the performance of blows during competitive activity or faster. The selection of exercises for the improvement of high-speed power abilities of boxers at the stage of specialised basic training taking into account individual features of boxers (selection of weights and number of repetitions, interval loads), had a positive influence on the level of development of high-speed power abilities of boxers. Indicators of exercises which characterise the level of development of general and special high-speed power training had statistically significant improvements in boxers of the experimental group in comparison with indicators before the experiment and with indicators of boxers of the control group after the experiment. This testifies to the effectiveness of the offered exercises which promote the improvement of the level of high-speed power abilities of boxers at the stage of specialised basic training.